Stereographic Analysis of Cleat Characteristics in Coal and its Controlling Forces - Sapto Heru Yuwanto; Muhammad Abdul Rifa’i (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
Cleat analysis plays a crucial role in coal mining, although it is often overlooked. Cleat is related to permeability and porosity, serving as a location for the accumulation of gases. In coal seams, cleats control slope stability and serve as pathways for gas and liquid flow. Therefore, the utilization of cleats in coal mining varies significantly, as it can determine mining patterns and serve as a guide for identifying the presence of Coal Bed Methane (CBM). This research was conducted in the village of Jebak and its surroundings, Muara Tembesi District, Batang Hari Regency, Jambi Province. Stereographic methods were used to identify controlling forces in coal structures based on field measurements of face cleats and butt cleats, resulting in the direction of controlling forces in ridge formation. Based on the results and lithological discussions at the research site, the lithology consists of sandstone interbedded with coal, mudstone, and mudstone with coal and fine sandstone inserts. Stereographic analysis of cleat measurements revealed that the resulting forces were compression forces from the Northeast to the Southwest and from the Southwest to the Southeast, indicating that the origin of the cleat falls into the category of Exogenic Cleat.